DELEGATION OF AUTHORITY FROM DOCTORS TO NURSES FROM A CRIMINAL ASPECT - Beni Satria (Sean Institute, 2023)
Health is a human right and is one of the elements of welfare that must be realized in accordance with the ideals of the Indonesian nation contained in Pancasila and the 1945 Constitution of the Republic of Indonesia, so that the maximum level of health can be realized for the entire community which is part of prosperity, legal support is required in the implementation of various activities in the health sector. This paper discussed a descriptive in nature, namely research that aims to describe something in a certain area and at a certain time. Descriptive legal study is in the form of exposure and to obtain a complete picture of the application of law. This study will use a qualitative approach to describe the current situation systematically and factually with the aim of explaining and solving the problem under study. The legal basis and force that allows for the delegation of authority from doctors to nurses in terms of criminal aspects, as well as the authority of doctors and nurses. The relationship between doctors and other health workers in public health center, especially in remote areas, is regulated in a law on the profession of doctors and nurses. The delegation of authority in remote community health centers arises due to limited health personnel, especially doctors. The seriousness of the government in carrying out the people's mandate is expected so that maximum service can be achieved and the health status of the Indonesian people is realized.